Total synthesis of an anticancer natural product (+/-)-peharmaline A and its analogues - Kulkarni, Akshay S.; Shingare, Rahul D.; Dandela, Rambabu; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2018)
First total synthesis of a rare beta-carboline-vasicinone hybrid alkaloid (+/-)-peharmaline A has been accomplished in just 3 steps starting from known compounds. Stereoselective Pictet-Spengler reaction to nitrogenated tertiary carbon center and one-pot construction of the tricyclic skeleton of vasicinone are the highlights of present synthesis. We have also synthesized structurally close analogues of the natural product by following the developed route.